ANALISIS EFIKASI DIRI DAN HASIL BELAJAR BERBASIS E-LEARNING PADA MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA - Stefania Baptis Seto; Lely Suryani; Maria Goretty Diciloam Bantas (Program Studi PGSD Universitas Flores, 2020)
The purpose of this study is to see the relationship between self-efficacy and e-learning-based learning results in students of semester 4 of Flores university mathematics education study program. The research method used in this study is quantitative research, with linear regression analysis using SPSS with a random sample of 40 fourth semester students. The data analysis techniques used are the Prerequisite Test (Kolmogorov–Smirnov Normality Test) and its research Hypothesis test using Pearson Bivariate correlation analysis with the help of SPSS. The results of this study show self-efficacy (X) has a positive influence on e-learning based Learning Results (Y) known from the results of correlation analysis obtained from the value of R count to X to Y of 0.895 and the value of significance between X to Y obtained two asterisks (**) so that there is a positive influence with a significance level of 1%. In other words, better or better self-efficacy will increase the learning outcomes of the students themselves.